Studi Dasar Nepenthes spp. di Taman Wisata Alam Bukit Tangkiling, Palangka Raya, Kalimantan Tengah, Indonesia - Muhammad Rizki; Helen Oktafiani; Desimaria Panjaitan (Buitenzorg: Journal of Tropical Science, 2025)
Pitcher plants (Nepenthes spp.) are carnivorous plants that flourish in the Bukit Tangkiling Nature Tourism Park (BTNTP), Palangka Raya, Central Kalimantan. Searches of global biodiversity databases and relevant literature revealed no prior records of Nepenthes from this area. This study aimed to document and provide a baseline record of Nepenthes species occurring within BTNTP. The study was conducted from March to May 2022 using exploration and purposive sampling methods to collect plant specimens. Three species, namely Nepenthes gracilis Korth, Nepenthes mirabilis (Lour.) Druce, and Nepenthes rafflesiana Jack, were recorded across various habitats, including scrub forest, heath forest, secondary forest, and peat forest, all below 100 m above sea level. These findings contribute to the species inventory of BTNTP and serve as a scientific reference for future ecological monitoring and management strategies aimed at maintaining habitat quality and supporting long-term Nepenthes conservation efforts in the region. Keywords: habitat, species record, pitcher plants, Nepenthes, Kalimantan